Radiological Hazard Assessment of Naturally Occurring Radioactive Materials in the Hwange Mining Area, Zimbabwe: A Gamma Spectrometric Study - Innocent Mayida; Manny Mathuthu; Vera Uushona; Robin Tinavo Mashingaidze (International Journal of Environmental Research and Public Health, 2026)
The Hwange Mining Area, located in the Mid-Zambezi Karoo Basin in northwestern Zimbabwe, is a major centre for coal mining, processing, and thermal power generation. This study evaluates the ecological and public health risks associated with these activities by characterising radionuclide (226Ra, 232Th, 40K) activity concentrations in coal and surrounding soils using Hyper-Pure Germanium (HPGe) gamma spectrometry. Samples were collected from four locations, as follows: Hwange Colliery Company (underground and open-cast mines), Zambezi Gas open-cast operations, residential areas, and the Zimbabwe Power Company (ZPC) thermal power station. Radionuclide concentrations were measured using Hyper-Pure Germanium (HPGe) gamma spectrometry. Mean activity concentrations in coal were low at both mining sites (Hwange Colliery: 226Ra 16 ± 5.3 Bq/kg), 232Th 14 ± 5.7 Bq/kg), (40K 51 ± 8.8 Bq/kg) and Zambezi Gas (226Ra 9.80 ± 2.3 Bq/kg), 232Th (11 ± 3.3 Bq/kg), 40K (43 ± 26 Bq/kg), well below UNSCEAR world coal averages. In contrast, soils from residential areas): 226Ra (36 ± 15 Bq/kg), 232Th (36 ± 12 Bq/kg) and 40K (220 ± 80 Bq/kg), and the ZPC power station (226Ra 47 ± 8.6 Bq/kg, 232Th (42 ± 10 Bq/kg), and 40K 230 ± 92 Bq/kg, showed markedly elevated concentrations, consistent with the accumulation of coal-combustion by-products such as fly ash. Radiological hazard indices remained within internationally accepted limits at all sites, as follows: radium equivalent (Raeq) ranged from 29 ± 6.7 Bq/kg (Zambezi Gas) to 120 ± 18 Bq/kg (ZPC), well below the 370 Bq/kg safety ceiling, while external and internal hazard indices (Hex, Hin) remained below unity throughout, peaking at 0.32 and 0.46, respectively, at ZPC. Annual effective dose equivalents (AEDE) ranged from 16 ± 3.8 to 69 ± 10 μSv/year, the latter (ZPC) representing approximately 7% of the ICRP public dose limit of 1 mSv/year. Excess lifetime cancer risk (ELCR) values ranged from 5.56 × 10−5 (Zambezi Gas) to 2.42 × 10−4 (ZPC), remaining below the global average outdoor reference of 0.29 × 10−3 but reaching approximately 83% of this reference at ZPC and 71% in residential areas. These findings indicate that, while coal mining activities in Hwange contribute minimally to environmental radioactivity, coal combustion at the ZPC thermal power station is the dominant driver of elevated radionuclide concentrations and radiological indices in the surrounding environment, with residential soils reflecting the same enrichment pathway. Although no immediate radiological hazard was identified at any location, the comparatively higher indices at ZPC and in nearby residential areas underscore the need for continuous environmental monitoring, strengthened regulatory control, and targeted radiation protection strategies to safeguard workers and nearby communities.